THE EFFECT OF EMOTIONAL INTELLIGENCE ON STUDENTS’ ACADEMIC ACHIEVEMENT (Study on Accounting Students of Brawijaya University) - Lestari, Putri Ayu Dwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of this study is to determine whether the components of emotional intelligence which consists of five categories, such as: (1). Self-Awareness, (2). Self-Regulation, (3). Motivation, (4). Empathy, and (5). Social Skills that are effect on students' academic achievement on accounting, Brawijaya University. This study uses primary data and secondary data. The primary data was used to measure emotional intelligence of accounting students using a questionnaire. Meanwhile, secondary data were obtained from the accounting department to get information about the total of active students majoring in accounting. This research is categorized as Causal Study because this study illustrates the cause of one or more problems. In other words, researcher is trying to link between variables. Using multiple regression analysis, the results obtained simultaneously showed that emotional intelligence does not significantly influence academic achievement. Partial test showed, that only empathy variable significantly affects academic achievement of accounting students.Keywords: Emotional Intelligence, Accounting Student Academic Achievement